(untitled) (Encuentros, 2019)
The limited integration between border universities, caused by the lack of policies and strategies to support knowledge alliances, constitutes the research argument. This seeks to establish a structure for integration, which contributes to the viability of the integral development of universities in cross-border territories. On the basis of explanatory and interpretative approaches, research was conducted, oriented towards the construction of the theoretical system based on conceptions, on intercultural identity, cross-border integration, internationalization; and finally the construction of scenarios, visualizing a future to 15 years. The results allowed to evaluate the potential of success of the academic-scientific integration processes, between the University of Zulia (Venezuela), the University of La Guajira and the Popular University of Cesar (Colombia) Keywords: integration; internationalization; border universities.